Proposed Marketing Strategy For Monsterstress Records - Darmawan, Gega; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract. Music markets are moving at different speeds with diverse trends in different countries. In ASIA the growth reached 3.6%, and the strong growth occurred in Indonesia which is 16.3%. Nowadays, the way people consume music has been switched to digital, music marketing was certainly shifted in the same direction. However, it is not as simple as moving the platforms from selling CD into digital download, the right marketing strategy for Monsterstress Records, an independent record label from Bandung, Indonesia needs to be done to deal with this challenge. The problems being faced by the company is low sales compared to competitors and it poor performance in the internal of the company. To identify the root cause of problems, this research uses quantitative methodology using the concept of STP (segmenting, targeting and positioning) and marketingâ€™s mix dimension to be applied into importance-performance analysis tool, after that researcher also identify the root cause using SWOT analysis. From the result, it can be concluded that the root cause of the problem is poor product quality and variance, lack of distribution channel, poor promotional activities, and poor organizational system. To overcome the root cause, the solutions are changing the target market and proposing new marketing strategy for Monsterstress Records. Changes occur target market in terms of geographic, demographic, psychographic, and behavioristic. Changes in the target market is the basis in proposing new strategy. New strategies for Monsterstress Records are recruiting new artist, release product in new physical format and digital format, new channel of distribution, new promotion arrangements and changing organizational structure and job description for each division to improve team performance. An implementation plan for applying new strategy is made in the form of a table plan. Implementation plan covering human resources and budgeting for the new strategies. This implementation began in January 2016 through June 2016.Â Keywords: Record Label, Sales, STP, Marketing Mix